Koch Fractal Loop Circular Polarization (CP) Antenna Integrated with Solar Cells - Alobaidi O.R.; Akhtaruzzaman M.; Selvanathan V.; Amin N. (IEEE Computer Society, 2023)
Cell membranes; Circular polarization; Economic and social effects; Efficiency; Electric fields; Fractals; Microwave antennas; Radio; Radio communication; Slot antennas; Solar cell arrays; Solar concentrators; Substrates; CST MWS; Frequency; Gain; Micro-strip patch antennas; RF performance; Solar panels; Transparent substrate; Wireless communications; Microstrip antennas